Surgical aortopulmonary shunts-a thirty-seven year experience in a South African tertiary institution - Dladla-Mukansi, N C (My University, 2021)
Introduction: The surgical aortopulmonary shunt is a valuable palliative procedure in the management of congenital heart diseases. There is a paucity of data regarding aortopulmonary shunts in the developing world, including South Africa. Objectives: The primary objective was to describe the demographic, clinical and echocardiographic characteristics of children between ages 0 and 14 years that underwent surgical aortopulmonary shunts. The secondary objectives were to describe trends in aortopulmonary shunt designs, outcomes in terms of morbidity and mortality, progression to definitive surgery and to assess patency of shunts. Material and Methods: A retrospective clinical audit of patient files who underwent an aortopulmonary shunt between 01 January 1980 to 30 December 2016 was undertaken at Chris Hani Baragwanath Academic Hospital (CHBAH) in Soweto, Johannesburg. The study period was divided into 3 stages and for descriptive purposes as follows: 1980-1991 refers to period 1, 1992-2003 refers to period 2 and 2004-2016 refers to period 3. Results: A total of 177 aortopulmonary shunts were done over the 37-year study period. Of these 177 patients, 165 (93.2%) patient files were available. Fifty-six percent of the patients included in the study were male. The majority of patients were from the Gauteng Province (76.8%).The four most common diagnoses across the entire study period were tricuspid atresia (26.0%), pulmonary atresia with VSD (23.7%), tetralogy of Fallot (23.2%) and complex cardiac lesions (16.9%), with no particular trend in the proportion of these diagnoses presenting across this study period. There was no statistical difference between period 1 and 2 (p-value a=0,328) and between period 1 and 3 (p-value b=0,548).The total number of all surgeries done over the entire study period was 2145, of which 8.3% were aortopulmonary shunts. Period 1 had the highest percentage [35 (10.9%)] of aortopulmonary shunts compared to the total number of surgeries performed. There was a decline in the number of aortopulmonary shunts performed over the study periods 1-3.With no statistical difference across periods as shown in table 1 with p-value a and b. Of the different types of aortopulmonary shunts, most patients [157 (88.7%)] had a modified Blalock-Taussig shunt (BTS).The remainder of the shunts included 3 (1.7%) classic BTS, 12 (6.8%) central shunts and 5 (2.8%) unknown BTS. The percentage of modified BTS done increased from 80% in period 1 to 87.3% in period 2 and to 95.2% in period 3. Period 1 had the most complications (28.6%) compared to 11.4% in period 2 and 19.1% in period 3. Sepsis as a complication following surgery increased over the study period from 2.9% in period 1 to 3.8% and 7.9% in periods 2 and 3 respectively. Early mortality was 17.1%, 26.6% and 25.4% from periods 1-3 respectively. Late mortality declined from 17.0% in period 1 to 11.4% and 0% in periods 2 and 3 respectively. Only 37 (20.9%) patients were documented to have further surgery after the initial aortopulmonary shunt. Across all three study periods, no blocked shunts were documented. Conclusions: This study describes the characteristics and outcomes of aortopulmonary shunts over a 37-year period in a tertiary care resource limited low to middle income country setting. The commonest cardiac lesions for which aortopulmonary shunts are performed are tricuspid atresia, pulmonary atresia with VSD, tetralogy of Fallot and other complex cyanotic cardiac lesions. The frequency of aortopulmonary shunts compared to total surgeries has decreased over the study period, which may imply a trend towards early corrective surgery for these cardiac lesions. The modified BTS is the most frequently performed aortopulmonary shunt used for palliative surgery in our setting, which is a similar trend in developed countries The morbidity and mortality in this study is higher than developed countries, with sepsis being the most common complication. Attention to infection control practises need to be emphasized peri-and post-operatively in our hospitals
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Paediatrics, 2021